A LC-HRMS method for drug exposure measurement of 57 oral anticancer drugs in human plasma - Kehl, Niklas; Dürr, Pauline; Schlichtig, Katja; Maas, Renke; Fromm, Martin; Geßner, Arne; Taudte, Verena (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

A supervised machine-learning approach for the efficient development of a multi method (LC-MS) for a large number of drugs and subsets thereof: Focus on oral antitumor agents - Kehl, Niklas; Geßner, Arne; Maas, Renke; Fromm, Martin; Taudte, Verena (Clinical Chemistry and Laboratory Medicine, 2023)
Accumulating evidence argues for a more widespread use of therapeutic drug monitoring (TDM) to support individualized medicine, especially for therapies where toxicity and efficacy are critical issues, such as in oncology. However, development of TDM assays struggles to keep pace with the rapid introduction of new drugs. Therefore, novel approaches for faster assay development are needed that also allow effortless inclusion of newly approved drugs as well as customization to smaller subsets if scientific or clinical situations require. We applied and evaluated two machine-learning approaches i.e., a regression-based approach and an artificial neural network (ANN) to retention time (RT) prediction for efficient development of a liquid chromatography mass spectrometry (LC-MS) method quantifying 73 oral antitumor drugs (OADs) and five active metabolites. Individual steps included training, evaluation, comparison, and application of the superior approach to RT prediction, followed by stipulation of the optimal gradient. Both approaches showed excellent results for RT prediction (mean difference ± standard deviation: 2.08 % ± 9.44 % ANN; 1.78 % ± 1.93 % regression-based approach). Using the regression-based approach, the optimum gradient (4.91 % MeOH/min) was predicted with a total run time of 17.92 min. The associated method was fully validated following FDA and EMA guidelines. Exemplary modification and application of the regression-based approach to a subset of 14 uro-oncological agents resulted in a considerably shortened run time of 9.29 min. Using a regression-based approach, a multi drug LC-MS assay for RT prediction was efficiently developed, which can be easily expanded to newly approved OADs and customized to smaller subsets if required.
CRIS-Team Scopus Importer:2023-09-15
Keywords: artificial neural networks; liquid chromatography coupled to mass spectrometry; oral antitumor drugs; plasma concentration; regression analysis; supervised machine-learning

Cancer-Type Organic Anion Transporting Polypeptide 1B3 Is Localized in Lysosomes and Mediates Resistance against Kinase Inhibitors - Haberkorn, Bastian; Oswald, Stefan; Kehl, Niklas; Geßner, Arne; Taudte, Verena; Dobert, Jan; Zunke, Friederike; Fromm, Martin; König, Jörg (Molecular Pharmacology, 2022)
Cancer-type organic anion transporting polypeptide 1B3 (CtOATP1B3), a splice variant of the hepatic uptake transporter OATP1B3 (liver-type), is expressed in several tumor entities, including colorectal carcinoma (CRC) and breast cancer. In CRC, high OATP1B3 expression has been associated with reduced progression-free and overall survival. Several kinase inhibitors used for antitumor treatment are substrates and/or inhibitors of OATP1B3 (e.g., encorafenib, vemurafenib). The functional importance of CtOATP1B3 has not been elucidated so far. Human embryonic kidney 293 cells stably overexpressing Ct-OATP1B3 protein were established and compared with control cells. Confocal laser scanning microscopy, immunoblot, and proteomics-based expression analysis demonstrated that Ct-OATP1B3 protein is intracellularly localized in lysosomes of stably transfected cells. Cytotoxicity experiments showed that cells recombinantly expressing the Ct-OATP1B3 protein were more resistant against the kinase inhibitor encorafenib compared with control cells [e.g., encorafenib (100 mM) survival rates: 89.5% versus 52.8%]. In line with these findings, colorectal cancer DLD1 cells endogenously expressing Ct-OATP1B3 protein had poorer survival rates when the OATP1B3 substrate bromosulfophthalein (BSP) was coincubated with encorafenib or vemurafenib compared with the incubation with the kinase inhibitor alone. This indicates a competitive inhibition of Ct-OATP1B3–mediated uptake into lysosomes by BSP. Accordingly, mass spectrometry-based drug analysis of lysosomes showed a reduced lysosomal accumulation of encorafenib in DLD1 cells additionally exposed to BSP. These results demonstrate that Ct-OATP1B3 protein is localized in the lysosomal membrane and can mediate transport of certain kinase inhibitors into lysosomes, revealing a new mechanism of resistance.
Created from Fastlane, Scopus look-up

Development and validation of an LC-MS method for drug exposure measurement of 57 oral antitumor drugs in human plasma - Kehl, Niklas; Dürr, Pauline; Schlichtig, Katja; Maas, Renke; Fromm, Martin; Geßner, Arne; Taudte, Verena (EUROPEAN JOURNAL OF CLINICAL PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-08

Exposure of Fexofenadine, but Not Pseudoephedrine, Is Markedly Decreased by Green Tea Extract in Healthy Volunteers - Misaka, Shingen; Ono, Yuko; Taudte, Verena; Hoier, Eva; Ogata, Hiroshi; Ono, Tomoyuki; König, Jörg; Watanabe, Hiroshi; Fromm, Martin; Shimomura, Kenju (Clinical Pharmacology & Therapeutics, 2022)
Green tea (GT) alters the disposition of a number of drugs, such as nadolol and lisinopril. However, it is unknown whether GT affects disposition of hydrophilic anti-allergic drugs. The purpose of this study was to investigate whether pharmacokinetics of fexofenadine and pseudoephedrine are affected by catechins, major GT components. A randomized, open, 2-phase crossover study was conducted in 10 healthy Japanese volunteers. After overnight fasting, subjects were simultaneously administered fexofenadine (60 mg) and pseudoephedrine (120 mg) with an aqueous solution of green tea extract (GTE) containing (−)-epigallocatechin gallate (EGCG) of 300 mg or water (control). In vitro transport assays were performed using HEK293 cells stably expressing organic anion transporting polypeptide (OATP)1A2 to evaluate the inhibitory effect of EGCG on OATP1A2-mediated fexofenadine transport. In the GTE phase, the area under the plasma concentration-time curve and the amount excreted unchanged into urine for 24 hours of fexofenadine were significantly decreased by 70% (P < 0.001) and 67% (P < 0.001), respectively, compared with control. There were no differences in time to maximum plasma concentration and the elimination half-life of fexofenadine between phases. Fexofenadine was confirmed to be a substrate of OATP1A2, and EGCG (100 and 1,000 μM) and GTE (0.1 and 1 mg/mL) inhibited OATP1A2-mediated uptake of fexofenadine. On the contrary, the concomitant administration of GTE did not influence the pharmacokinetics of pseudoephedrine. These results suggest that intake of GT may result in a markedly reduced exposure of fexofenadine, but not of pseudoephedrine, putatively by inhibiting OATP1A2-mediated intestinal absorption.
CRIS-Team Scopus Importer:2022-07-08

Headspace analysis of E-cigarette fluids using comprehensive two dimensional GC×GC-TOF-MS reveals the presence of volatile and toxic compounds - Patel, Darshil; Taudte, Verena; Nizio, Katie; Herok, George; Cranfield, Charles; Shimmon, Ronald (Journal of Pharmaceutical and Biomedical Analysis, 2021)
The analysis of electronic cigarrete (E-cigarette) fluids by high performance liquid chromatography or gas chromatography (GC) coupled to mass spectrometry (MS), GC hyphenated to flame-ionisation detection, or nuclear magnetic resonance spectroscopy poses many challenges due to the complex matrix and extremely high number of compounds present. In order to overcome these challenges, this study focused on the detection of the multiple complex compounds classes produced by the pyrolysis of E-cigarette liquids using comprehensive two dimensional gas chromatography (GCxGC) coupled to time of flight (TOF)-MS. Gas samples were prepared by heating E-liquids inside aluminium tins for 5 min. The tins were placed in a sand bath, which was temperature controlled at 200 °C. The samples were collected using thermal desorption tubes connected to volatile organic compound (VOC) sampling pump attached and subsequently analysed using GCxGC-TOF-MS. The greater peak resolution obtained when using GCxGC-TOF-MS allowed to distinguish many toxic compounds and VOCs that could not be detected by the other methods mentioned above. As a result, a comprehensive list of volatile compounds emitted from E-cigarette fluids when heated was established, which might allow a better understanding of potential health effects of vaping. Heating E-liquids to moderate temperature results in the emission of over 1000 volatile compounds of which over 150 are toxic. These compounds are either present in the liquid or can be formed during storage or heating leading to a more complex volatile profile of E-cigarette liquids than previously assumed. The application of GCxGC-TOF-MS allows the elucidation of this profile and therefore a better understanding of possible health implications.
CRIS-Team Scopus Importer:2021-03-19
Keywords: E-cigarette; E-cigarette fluids; Toxic chemicals; Two dimensional GCxGC-TOF-MS; VOCs

High-fat-diet-associated intestinal microbiota exacerbates psoriasis-like inflammation by enhancing systemic γδ T cell IL-17 production - Sonomoto, Koshiro; Song, Rui; Eriksson, Daniel; Hahn, Anne Maria; Meng, Xianyi; Lyu, Pang; Cao, Shan; Liu, Ning; Taudte, Verena; Wirtz, Stefan; Tanaka, Yoshiya; Winkler, Thomas; et al. (Cell Reports, 2023)
Although it is known that psoriasis is strongly associated with obesity, the mechanistic connection between diet and skin lesions is not well established. Herein, we showed that only dietary fat, not carbohydrates or proteins, exacerbates psoriatic disease. Enhanced psoriatic skin inflammation was associated with changes in the intestinal mucus layer and microbiota composition by high-fat diet (HFD). Change of intestinal microbiota by vancomycin treatment effectively blocked activation of psoriatic skin inflammation by HFD, inhibited the systemic interleukin-17 (IL-17) response, and led to increased mucophilic bacterial species such as Akkermansia muciniphila. By using IL-17 reporter mice, we could show that HFD facilitates IL-17-mediated γδ T cell response in the spleen. Notably, oral gavage with live or heat-killed A. muciniphila effectively inhibited HFD-induced enhancement of psoriatic disease. In conclusion, HFD exacerbates psoriatic skin inflammation through changing the mucus barrier and the intestine microbial composition, which leads to an enhanced systemic IL-17 response.
CRIS-Team Scopus Importer:2023-07-28
Keywords: CP: Immunology; CP: Microbiology; high-fat diet; psoriasis; γδT cell

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

L-ARGININE REPROGRAMS OSTEOCLAST PURINE METABOLISM AMELIORATING BONE LOSS IN RHEUMATOID ARTHRITIS - Cao, Shan; Song, Rui; Meng, Xianyi; Kachler, Katerina; Fuchs, Maximilian; Meng, X.; Li, Y.; Taudte, Verena; Kunz, Meik; Schlötzer-Schrehardt, Ursula; Schleicher, Ulrike; Chen, X.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Matching sensitivity to abundance: High resolution immuno-mass spectrometry imaging of lanthanide labels and endogenous elements in the murine brain - Clases, David; De Vega, Raquel Gonzalez; Funke, Sabrina; Lockwood, Thomas E.; Westerhausen, Mika T.; Taudte, Verena; Adlard, Paul A.; Doble, Philip A. (Journal of Analytical Atomic Spectrometry, 2020)
This work introduces a new method for immuno-mass spectrometry imaging via quadrupole-based laser ablation-inductively coupled plasma-mass spectrometry instruments that is matched to the abundance of elements in biological tissues. Manipulation of ion-optics and quadrupole mass filter parameters provided increased transmission of low level high-mass elements, which are typically used as labels for antibodies, at the expense of highly abundant endogenous low-mass elements. Transmission of mid-mass elements such as transition metals was only slightly affected. The implications for mass resolution and background signals are critically discussed and signal to noise ratios and imaging capabilities are compared to those obtained from a standard method. This novel approach resulted in a 6-fold improved signal to noise ratio for lanthanides that are routinely used as elemental labels for antibodies to target protein distributions in biological tissues. This increase in signal intensity, enhanced contrasts, lower limits of detection and the potential to improve spatial resolution contributed to enhanced imaging and trace analyses, as demonstrated by imaging murine brain sections of the hippocampal system and substantia nigra.
CRIS-Team Scopus Importer:2020-04-24

Metabolic rewiring controlled by HIF-1α tunes IgA-producing B-cell differentiation and intestinal inflammation - Meng, Xianyi; Asadi Asadabad, Sahar; Cao, Shan; Song, Rui; Lin, Zhen; Safhi, Mohammed; Qin, Yi; Tcheumi Tactoum, Estelle Manuella; Taudte, Verena; Ekici, Arif Bülent; Mielenz, Dirk; Wirtz, Stefan; et al. (Cellular & Molecular Immunology, 2024)
Germinal centers where B cells undergo clonal expansion and antibody affinity maturation are hypoxic microenvironments. However, the function of hypoxia-inducible factor (HIF)-1α in immunoglobulin production remains incompletely characterized. Here, we demonstrated that B cells lacking HIF-1α exhibited significantly lower glycolytic metabolism and impaired IgA production. Loss of HIF-1α in B cells affects IgA-producing B-cell differentiation and exacerbates dextran sodium sulfate (DSS)-induced colitis. Conversely, promoting HIF-1α stabilization via a PHD inhibitor roxadustat enhances IgA class switching and alleviates intestinal inflammation. Mechanistically, HIF-1α facilitates IgA class switching through acetyl-coenzyme A (acetyl-CoA) accumulation, which is essential for histone H3K27 acetylation at the Sα region. Consequently, supplementation with acetyl-CoA improved defective IgA production in Hif1a-deficient B cells and limited experimental colitis. Collectively, these findings highlight the critical importance of HIF-1α in IgA class switching and the potential for targeting the HIF-1α-dependent metabolic‒epigenetic axis to treat inflammatory bowel diseases and other inflammatory disorders.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B cells; HIF-1α; Hypoxia; IgA; Intestinal inflammation

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Propionate induced bacterial-derived histamine promotes resolution of synovial inflammation - Dürholz, Kerstin; Lucas, Sébastien; Schmid, Eva; Schaelter, F.; Frech, Michael; Azizov, Vugar; Hofmann, Jörg; Iljazovic, A.; Strowig, T.; Taudte, Verena; Fromm, Martin; Xiang, Wei; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Regiospecific Introduction of Halogens on the 2-Aminobiphenyl Subunit Leading to Highly Potent and Selective M3 Muscarinic Acetylcholine Receptor Antagonists and Weak Inverse Agonists - Fischer, Oliver; Hofmann, Josefa; Rampp, Hannelore; Kaindl, Jonas; Pratsch, Gerald; Bartuschat, Amelie; Taudte, Verena; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2020)
Muscarinic M-3 receptor antagonists and inverse agonists displaying high affinity and subtype selectivity over the antitarget M-2 are valuable pharmacological tools and may enable improved treatment of chronic obstructive pulmonary disease (COPD), asthma, or urinary incontinence. On the basis of known M-3 antagonists comprising a piperidine or quinuclidine unit attached to a biphenyl carbamate, S-fluoro substitution was responsible for M-3 subtype selectivity over M-2, while 3'-chloro substitution substantially increased affinity through a sigma-hole interaction. Resultantly, two piperidinyl- and two quinuclidinium-substituted biphenyl carbamates OFH243 (13n), OFH244 (13m), OFH3911 (14n), and OFH3912 (14m) were discovered, which display two-digit picomolar affinities with K-i values from 0.069 to 0.084 nM, as well as high selectivity over the M-2 subtype (46- to 68-fold). While weak inverse agonistic properties were determined for the biphenyl carbamates 13m and 13n, neutral antagonism was observed for 14m and 14n and tiotropium under identical assay conditions.
CRIS-Team WoS Importer:2020-05-15

Vectorial transport of the arginine derivatives asymmetric dimethylarginine (ADMA) andl-homoarginine by OATP4C1 and P-glycoprotein studied in double-transfected MDCK cells - Taghikhani, Emir Puyan; Maas, Renke; Taudte, Verena; Geßner, Arne; Fromm, Martin; König, Jörg (Amino Acids, 2020)
Elevated plasma concentrations of the uremic toxin asymmetric dimethylarginine (ADMA) and low plasma concentrations ofl-homoarginine are independently associated with cardiovascular events and mortality. Key enzymes involved in the homeostasis of both arginine derivatives are expressed in proximal tubule cells of the kidney. To get access to these enzymes, transport proteins are important. One of the transporters mediating the transport of ADMA andl-homoarginine is the solute carrier superfamily (SLC) member OATP4C1, located in the basolateral membrane of proximal tubule cells. To gain insights into the role of export pumps in the transport of both substances, we established a double-transfected MDCK cell line expressing OATP4C1 and the export pump P-glycoprotein (P-gp). Using MDCK cell monolayers, we demonstrated in time-dependent and concentration-dependent vectorial transport experiments that ADMA andl-homoarginine are transported from the basolateral to the apical compartment of MDCK-OATP4C1-P-gp cells with significantly higher transport rates compared to single-transfected MDCK-OATP4C1, MDCK-P-gp and MDCK-VC (control) cells (e.g. transport ratio MDCK-OATP4C1-P-gp/MDCK-VC: for 50 mu M ADMA = 2.0-fold, for 50 mu Ml-homoarginine = 3.4-fold). These results indicate that both OATP4C1 and P-gp transport the arginine derivatives ADMA andl-homoarginine and are, therefore, important for the homoeostasis of both substances.
CRIS-Team WoS Importer:2020-07-17